2023
DOI: 10.26434/chemrxiv-2023-nb5jj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antimony-bismuth alloying: the key to a major boost in the efficiency of lead-free perovskite-inspired indoor photovoltaics

Abstract: Perovskite-inspired Cu2AgBiI6 (CABI) absorber has recently gained increased popularity due to its low toxicity, intrinsic air stability, and wide bandgap ≈ 2 eV, which makes it ideal for indoor photovoltaics (IPVs). However, the considerable presence of both intrinsic and surface defects is responsible of the still modest indoor power conversion efficiency (PCE(i)) of CABI- based IPVs, with the short-circuit current density (JSC) being nearly half of the theoretical limit. Herein, we introduce antimony (III) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…This suggests the involvement of Bi lattice sites in CABI emission. This is in line with the suppression of the STE emission through partial substitution of Sb 3+ into [BiI 6 ] 3– units of CABI crystal structure, which, in turn, suggests that distortion of [BiI 6 ] 3– in the excited state produces the STE state. Moreover, the bottom of the conduction band of CABI is dominated by Bi 6p and I 5p states .…”
supporting
confidence: 73%
See 2 more Smart Citations
“…This suggests the involvement of Bi lattice sites in CABI emission. This is in line with the suppression of the STE emission through partial substitution of Sb 3+ into [BiI 6 ] 3– units of CABI crystal structure, which, in turn, suggests that distortion of [BiI 6 ] 3– in the excited state produces the STE state. Moreover, the bottom of the conduction band of CABI is dominated by Bi 6p and I 5p states .…”
supporting
confidence: 73%
“…These findings suggest a complex STE emission mechanism occurring in CABI. Very recently, by coalloying antimony(III) (Sb 3+ ) with Bi 3+ in CABI, we successfully quenched the STE emission of CABI, in turn significantly boosting the J SC of CABI-Sb IPVs, which achieved a bold PCE(i) of nearly 10% . This clearly suggests that the suppression of the self-trapping of the charge carriers is crucial to enhance the performance of CABI-based devices.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fulfilling this prediction, AgBiI 4 -based indoor photovoltaics with an efficiency of up to 5.2% was subsequently demonstrated [81]. Most recently, emerging Cu-Ag-Bi-I-based absorbers with near optimum bandgap for indoor photovoltaics have been shown to deliver PCE(i) values of up to 9.53% [82][83][84], thereby highlighting the considerable indoor photovoltaic potential of copper-silver pnictohalides [79]. Furthermore, a hybrid absorber combining Cs 3 Sb 2 I 9 and an organic molecule, ITIC, was reported to deliver PCE(i) values of up to 9.2% [85].…”
Section: Statusmentioning
confidence: 92%
“…However, the low indoor V OC values of just B0.6 V in these devices are due to already low V OC values achieved under 1-Sun, particularly in the case of CABI. [24][25][26]28 Hoye and co-workers examined the performance limiting factors of Cs 2 Ag(Sb x Bi 1Àx )Br 6 solar cells. 54 They demonstrated that sub-band gap states are accountable for the V OC losses.…”
Section: Suppressed Carrier Self-trapping Is Necessarymentioning
confidence: 99%